Dwubiegunowość postaw wobec zjawiska migracji i ich odzwierciedlenie w języku dyskursu medialnego - Majewska-Zarychta, Joanna (Migracja w języku, literaturze i kulturze, 2020)
This article presents the attitudes of persons who are friendly and unfriendly towards migration phenomenon. These attitudes are on two opposite poles, from extremely positive to extremely negative. Both in everyday language as well as in the media language or the language of the elite one can notice this outlined bipolarity of attitudes. The article discusses the definition of attitude as an element of intercultural communication that shapes relationships on the international stage. The pro and contra arguments present the complexity of the migration phenomenon. Contra arguments are reinforced by stereotypes about migrants, which were described using examples from the media. The evidence of a strong polarization of attitudes and above all a negative attitude towards migration is given by numerous examples of hate speech in socio-political discourse. It appears in both liberal, leftist and rightist magazines. This phenomenon seems interesting from a linguistic point of view, but one needs to know that it is associated with various social tensions which also affect language.